DOMESTIC WASTE DISPOSAL PRACTICES AND AWARENESS ABOUT ITS IMPACTS ON ENVIRONMENT AND HUMAN HEALTH IN AN ISLANDIC VILLAGE: AKHADA-ST. ESTEVAM IN GOA (Prakriti - The International Multidisciplinary Research Journal, 2025)
Effective domestic or household waste management is crucial for environmental sustainability  and public health. Improper disposal practices lead to adverse sanitation, pollution, disease  outbreaks and ecosystem degradation. This study examines waste disposal practices and  awareness level among the households in a selected village in Tiswadi taluka of Goa. While  residents show high awareness of the harmful effects of improper waste management, a  significant gap exists between knowledge and action. Factors such as poor recycling habits,  lack of infrastructure for waste disposal and limited public education contribute to this  issue. By analysing household behaviours and perceptions, the study aims to recommend  strategies for improving waste management practices and enhancing community health and  sustainability. Improper waste disposal continues to pose significant environmental and public  health challenges contributing to pollution, fear of disease outbreaks and the degradation of  ecosystems. This study evaluates household waste management practices, awareness levels,  and perceptions among 60 respondents from a selected village. Data collection was facilitated  through structured questionnaires and findings were analysed using tables and visualized  through pie charts created in Microsoft Excel to better understand patterns and trends.  A majority of respondents reported suffering from allergies due to waste exposure, and  many experienced infectious diseases, highlighting immediate health threats stemming from  poor waste management. The study also found that while several respondents consistently  separated waste, a considerable number displayed inconsistent segregation practices. Daily  waste disposal was commonly observed among households, reflecting regular management  efforts; however, recycling habits remained poor, with most respondents rarely recycling and  none reporting frequent recycling. Many individuals reused plastic bags, which is a positive  trend, yet harmful practices like burning plastic and dumping in water bodies still persist  among a minority. The findings suggest that there is lack of confidence in local government initiatives and poor  recycling support. The study recommends strengthening institutional waste management  support, expanding public education initiatives focused on sanitary and household waste  disposal, improving waste segregation facilities and promoting community engagement to  bridge the gap between knowledge and practice. Addressing these issues is crucial to ensuring  sustainable development in the studied communities.
Keywords: Waste Manage ment; Domestic Waste Dis posal; Environmental Health; Sanitary Waste; Improper Waste Disposal; Public Health Risks